Literature Review Dimensi Etika Dalam Manajemen Keperawatan Serta Pengaruhnya Terhadap Kepemimpinan Dan Profesionalisme - Muhammad Reza Fahlevi Hanafi; Arfah May Syara (Journal of Innovative and Creativity, 2025)
This literature review explores the ethical dimensions of nursing management and their influence on leadership and professionalism. The study aims to synthesize current findings on how ethical values—such as justice, integrity, responsibility, honesty, and empathy—are integrated into nursing leadership practices. A total of 12 peer-reviewed articles published between 2020 and 2025 were analyzed using a thematic synthesis approach. The results reveal that these ethical dimensions consistently underpin effective leadership and contribute to staff morale, decision-making quality, and organizational culture. However, challenges such as bureaucratic pressure, power imbalance, and the lack of formal ethical leadership training hinder consistent implementation. The findings suggest that ethical leadership is not only a moral ideal but a managerial competence that can be developed through education and structural support. The review highlights the need for healthcare institutions to incorporate ethical leadership development into both policy and practice to enhance nursing management outcomes.